Benefits and Risks of IgG Transplacental Transfer - Anca Marina Ciobanu; Andreea Elena Dumitru; Nicolae Gica; Radu Botezatu; Gheorghe Peltecu; Anca Maria Panaitescu (Diagnostics, 2020)
Maternal passage of immunoglobulin G (IgG) is an important passive mechanism for protecting the infant while the neonatal immune system is still immature and ineffective. IgG is the only antibody class capable of crossing the histological layers of the placenta by attaching to the neonatal Fc receptor expressed at the level of syncytiotrophoblasts, and it offers protection against neonatal infectious pathogens. In pregnant women with autoimmune or alloimmune disorders, or in those requiring certain types of biological therapy, transplacental passage of abnormal antibodies may cause fetal or neonatal harm. In this review, we will discuss the physiological mechanisms and benefits of transplacental transfer of maternal antibodies as well as pathological maternal situations where this system is hijacked, potentially leading to adverse neonatal outcomes.